Reconstruction of Traumatic Partial Ear Amputations Using Two-Stage Skin Flap Pocket Technique - Hakim, Intan Friscilla; Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, Kristaninta (Jurnal Plastik Rekonstruksi, 2013)
Background: Various reconstructive techniques for partial traumatic ear amputations have been reported. The choice of technique is based on the missing ear components and the availability of tissue for defect coverage. The goal is to obtain an aesthetically acceptable ear. The authors report a two-stage skin flap pocket technique for the reconstruction of traumatic ear amputations. Patient and Method: Three cases of partial traumatic ear amputation due to bite is reported. After sufficient debridement, skin flap pocket was created on the retroauriculomastoid area. Conchal cartilage graft was used to replace cartilage defect in one case. The other 2 cases utilized their amputated cartilage graft, deepithelialized and then resutured to the remaining cartilage. All three cases underwent second stage surgeries for flap division, three weeks after the pocketing. Result: In 2 months follow-up, all of 3 cases showed no signs of infection. Normal dimension of the ears were achieved and aesthetic appearances were perceived as acceptable to the patients and other viewers. One case was able to be followed one year post surgery with acceptable aesthetics, and no sign of cartilage resorption. Summary: The technique used in these cases provided acceptable results in reconstructing the size and shape of the partially amputated ears. Cartilage grafts implanted in the pockets retained their shape with no infection or resorption.